Pemanfaatan Aplikasi Whatsapp sebagai Media Pembelajaran Berbasis Distance Learning - M. Anas Hidayat; Ahmad Faiz Mahbubi Addaraini; M. Redho Rahman; Danial Hilmi (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2021)
The Whatsapp (WA) application has become the most popular social media in the world which was started due to features that are easy and flexible to use for daily communication. One very useful feature is the group chat feature, where users can create private groups and can be devoted to anything, including educational purposes. With its advantages, Whatsapp has become widely used as a learning medium. The purpose of this study is to describe the use of the Whatsapp application in distance learning-based learning and the researcher uses class E MPBA UIN Malang as the object of this research. The type of this research is descriptive qualitative research. The results of this study describe first, the implementation of the use of Whasapp as a learning medium, second, the obstacles to using the Whatsapp application in distance learning-based learning in class E MPBA UIN Malang, and third, the solution for using Whatsapp applications in distance learning-based learning in class E MPBA UIN Malang.